Makna Cinta dalam Puisi Nizar Qabbani dan Chairil Anwar: Kajian Sastra Bandingan - Basyayif, Syamil; Tasnimah, Tatik Mariyatut (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Nizar Qabbani and Chairil Anwar as modern poets of different nationalities, wrote many love poems. Although they write with the same theme, the views, conventions, or poetic traditions of Arab society and Indonesian society tend to be different. Based on that, this research aims to reveal the differences and similarities in the meaning of love in the poems “Yaumiyat Rajulin Mahzumin” and “`Ala `Ainaiki Yudabitu al-`Alam Sa`atihi” collected in the poetry anthology al-A`mal ash-Syi`riyah al-Kamilah by Nizar Qabbani, as well as the poems “Sajak Putih” and “Kabar dari Laut” collected in the poetry anthology Aku Ini Binatang Jalang by Chairil Anwar. This research uses the study of Thematic Parallelism in comparative literature that highlights the similarities and contrasts of themes, motifs, and main ideas between two or more works of poetry from different cultural contexts, periods, or languages. In interpreting the four poems above, the method used is Riffaterre's semiotics which consists of Heuristic reading and Hermeneutic reading. The results showed that there are similarities in the views of Nizar Qabbani and Chairil Anwar regarding the meaning of love, loyalty and sincerity, while the difference lies in Nizar Qabbani's pessimistic and Chairil Anwar's optimistic tendencies in viewing love.